2021
DOI: 10.1371/journal.pone.0245149
|View full text |Cite
|
Sign up to set email alerts
|

Increase in white blood cell counts by pegbovigrastim in primiparous and multiparous grazing dairy cows and the interaction with prepartum body condition score and non-esterified fatty acids concentration

Abstract: The objective of this study was to determine if parity affected the effect of pegbovigrastim (PEG) treatment on white blood cell (WBC) counts in grazing dairy cows. Additionally, the association of prepartum body condition score (BCS) and non-esterified fatty acid (Pre-NEFA) concentration with WBC counts was investigated. The effect of early-lactation disease was included in the statistical analysis. A randomized controlled trial on four commercial grazing dairy farms was performed. Holstein primiparous (Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…A more robust vaginal discharge due to a greater intra-uterine neutrophil influx in PEG treated cows was suggested by Ruiz et al [ 13 ]. This hypothesis is supported by the findings of lower blood neutrophil counts [ 11 ] and higher neutrophil counts in the vagina in PEG cows with metritis compared to PEG cows without metritis [ 14 ]. As expected [ 22 ], primiparous cows had a higher metritis occurrence, while no treatment by parity interaction was detected.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…A more robust vaginal discharge due to a greater intra-uterine neutrophil influx in PEG treated cows was suggested by Ruiz et al [ 13 ]. This hypothesis is supported by the findings of lower blood neutrophil counts [ 11 ] and higher neutrophil counts in the vagina in PEG cows with metritis compared to PEG cows without metritis [ 14 ]. As expected [ 22 ], primiparous cows had a higher metritis occurrence, while no treatment by parity interaction was detected.…”
Section: Discussionmentioning
confidence: 68%
“…This suggests that PEG has a differential effect according to the Pre-NEFA category. We expected a stronger association based on our recent findings that PEG reverts the negative association between Pre-NEFA and neutrophil counts [ 11 ]. Analysis of the estimated least squares means differences by Pre-NEFA category shows that, in high Pre-NEFA cows, PEG treatment significantly reduced the occurrence of a first case of CM during the first 30 d of lactation by 35%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed that treatment with PEG prevented the negative association of prepartum NEFA concentration with postpartum neutrophil counts (Barca et al, 2021a). In addition, we found that PEG reduced the occurrence of a first case of CM during the first 30 DIM, particularly in cows with elevated prepartum NEFA concentrations and in cows with excessive prepartum BCS (Barca et al, 2021b).…”
Section: Introductionmentioning
confidence: 65%
“…Metabolites related to negative energy balance (NEB), such as nonesterified fatty acids (NEFA) and BHB, have been identified as immunosuppressants (Ingvartsen and Moyes, 2015). Elevated NEFA concentrations were associated with decreased white blood cell and neutrophil counts (Hachenberg et al, 2007;Barca et al, 2021a) and impaired neutrophil and lymphocyte function (Lacetera et al, 2005;LeBlanc, 2020). Moreover, epidemiological studies have shown that elevated NEFA concentrations are associated with increased risk of diseases such as mastitis, retained placenta (RP), and metritis (LeBlanc et al, 2004;Melendez et al, 2009;Galvão et al, 2010).…”
Section: Introductionmentioning
confidence: 99%